Symmetry analysis of angle-resolved photoemission: Polarization dependence and lateral interactions in chemisorbed benzene - Nyberg, Graeme L.; Richardson, Neville V. (Surface science, 1979)
Using an oriented free-molecule model, exact selection rules are used to determine which bands are allowed in both normal and off-normal emission as a function of polarization direction. An approximate angular analysis of the final states is then applied to give a qualitative account of the emission angle dependence. The consequences of both inter- and intra-ad sorbate unit cell lateral interactions are considered, with effects which are new to adsorbate photoemission. When applied to benzene-on-Pd(100) angle-resolved spectra these concepts are shown to give a very adequate description of the results. Previous assignments are confirmed with the exception that the second π-orbital is now located on the leading edge of the C-band, thus implying that both π-orbitals are subject to similar adsorbate-substrate binding shifts. In conjunction with LEED data a specific adsorbate geometry is proposed.